The inequality of electoral participation in Europe and America and the politically integrative functions of the welfare state - Jens Alber; Ulrich Kohler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
Electoral turnout is shown to be higher and less socially skewed in member states of the enlarged European Union than in the United States. The differences in the levels of turnout can partly be related to differences in election procedures, but since the procedural rules provide similar incentives or disincentives to all social groups they cannot explain the much higher inequality of electoral participation in America. There is some evidence to sustain the notion that the higher inclusiveness of the West European welfare state fosters political integration and the equality of electoral participation. In line with this notion differences between Europe and America diminish considerably when the analysis is confined to the pensioner generation whose integration into welfare state schemes is largely similar on both sides of the Atlantic.
Keywords: 300; Wahlverhalten; Partizipation; Soziale Ungleichheit; Soziale Schicht; Rentner; Politisches System